The atlas of human rights : mapping violations of freedom around the globe - Fagan, Andrew (Berkely : University of California Press, 2010)
This timely atlas reveals human rights inequities from nation to nation and the consequences of these violations worldwide.
Includes bibliographical references and index.
Keywords: Human rights